(untitled) (Scientific journal of the Fergana State University, 2024)
The final results of experimental studies on introducing theoretical knowledge to science and increasing its effectiveness by organizing and conducting the educational material “Fundamentals of Theoretical Knowledge” in the school physical education curriculum as a separate theoretical lesson are summarized.